The bonding hypothesis of takeover defenses: Evidence from IPO firms - Johnson, William C.; Karpoff, Jonathan M.; Yi, Sangho (Journal of Financial Economics, 2015)
We propose and test an efficiency explanation for why firms deploy takeover defenses using initial public offering (IPO) firm data. We hypothesize that takeover defenses bond the firm׳s commitments by reducing the likelihood that an outside takeover will change the firm׳s operating strategy and impose costs on its business partners. Consistent with this hypothesis, we find that IPO firms deploy more takeover defenses when they have important business relationships to protect. An IPO firm׳s use of takeover defenses is positively related to the longevity of its business relationships. IPO firms’ use of takeover defenses creates positive spillovers for their large customers. And IPO firms’ valuation and subsequent operating performance are positively related to their use of takeover defenses when they have important business relationships.